2009
DOI: 10.1186/1471-2334-9-215
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 subtype and viral tropism determination for evaluating antiretroviral therapy options: an analysis of archived Kenyan blood samples

Abstract: BackgroundInfection with HIV-1 is characterized by genetic diversity such that specific viral subtypes are predominant in specific geographical areas. The genetic variation in HIV-1 pol and env genes is responsible for rapid development of resistance to current drugs. This variation has influenced disease progression among the infected and necessitated the search for alternative drugs with novel targets. Though successfully used in developed countries, these novel drugs are still limited in resource-poor count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 30 publications
5
13
0
Order By: Relevance
“…In addition, they are rarely observed in either drug naïve (<1%) or treatment-experienced patients (<5%) with preserved immunefunction (Brumme et al, 2005;Melby et al, 2006;Moyle et al, 2005;Wilkin et al, 2007;Simon et al, 2010). Conversely, a quite high proportion of patients harbouring dual/mixed-tropic viruses has been observed both in drug-naïve (prevalence ranging 12-15%) and in treatment-experienced patients (prevalence ranging 20-50%) (Church et al, 2008;Huang et al, 2007;Lihana et al, 2009;Moreno et al, 2009;Shepherd et al, 2008).…”
mentioning
confidence: 99%
“…In addition, they are rarely observed in either drug naïve (<1%) or treatment-experienced patients (<5%) with preserved immunefunction (Brumme et al, 2005;Melby et al, 2006;Moyle et al, 2005;Wilkin et al, 2007;Simon et al, 2010). Conversely, a quite high proportion of patients harbouring dual/mixed-tropic viruses has been observed both in drug-naïve (prevalence ranging 12-15%) and in treatment-experienced patients (prevalence ranging 20-50%) (Church et al, 2008;Huang et al, 2007;Lihana et al, 2009;Moreno et al, 2009;Shepherd et al, 2008).…”
mentioning
confidence: 99%
“…The presence of 3 of the following mutations M41L, D67N, L210W, T215Y/F, and K219Q/E has been associated with resistance to didanosin [6]. The presence of these mutations may improve subsequent virologic response to NNRTI-containing regimens (nevirapine or efavirenz) in NNRTI-naive individuals, although no clinical data exist for improved response to etravirine in NNRTI experienced individuals.…”
Section: Drug Resistance Mutations In Arv Experiencedmentioning
confidence: 99%
“…As ART use increases there is mounting evidence suggesting that DR will increase over time [6]. A recent cross-sectional study to determine treatment failure and drug resistance mutations among adults receiving first-line (3TC_d4T/AZT_NVP/EFV) and second-line (3TC/AZT/LPV/r) in Nairobi, Kenya, concluded that the detected accumulated resistance strains due to emergence of HIV drug resistance will continue to be a big challenge [7].…”
Section: Introductionmentioning
confidence: 99%
“…Group M is divided into several subtypes, which until now has been recognized several subtypes, namely A1, A2, A3, A4, B, C, D, F1, F2, G, H, J, and K. 1 Between a subtype with other subtypes can form the so-called recombinant CRF (circulating Recombinant Form) and, until now, 43 CRF has been found. 2 Differences in the characteristics of subtypes of the virus and its interactions with the human host may influence the severity of the disease. Some studies proposed that the HIV subtype variation associated with the clinical stage of disease.…”
Section: Introductionmentioning
confidence: 99%